2003
DOI: 10.1097/00006324-200303000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Component Data in Schoolchildren as a Function of Age and Gender

Abstract: These cross-sectional data show a general pattern of ocular growth, no change in corneal power, and crystalline lens thinning and flattening between the ages of 6 and 14 years. Girls tended to have steeper corneas, stronger crystalline lenses, and shorter eyes compared with boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
163
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(200 citation statements)
references
References 19 publications
27
163
7
Order By: Relevance
“…The multi‐ethnic Collaborative Longitudinal Evaluation of Ethnicity and Refractive Error (CLEERE) study conducted in the US found a prevalence of 11.6% (≤−0.75 D in both meridians) in 10‐year‐old (Zadnik et al. 2003), and the Australian Sydney Myopia Study found a prevalence of 11.9% (≤−0.50 D) in 13‐year‐old (Ip et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The multi‐ethnic Collaborative Longitudinal Evaluation of Ethnicity and Refractive Error (CLEERE) study conducted in the US found a prevalence of 11.6% (≤−0.75 D in both meridians) in 10‐year‐old (Zadnik et al. 2003), and the Australian Sydney Myopia Study found a prevalence of 11.9% (≤−0.50 D) in 13‐year‐old (Ip et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To test for concordance of our results with other studies conducted in other geographic regions, we extracted data from 13 other population‐based and school‐based studies that were conducted in North America (Zadnik et al. 2003), Europe (Larsen 1971; Rudnicka et al. 2010; Li et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The global pattern indicates that by age 12-15, the prevalence of the condition has fallen off substantially to low levels. [2][3][4][5][6][7][8][9][10][11][12] Although moderate-to-high hyperopia may coexist with strabismus 5 and associated with the risk of developing amblyopia 5 or angle closure glaucoma in later life, it appears that, given the relatively low prevalence of the condition, there is a paucity of information relating to the condition and its risk factors, and thus strategies to modify and control hyperopia have been limited. There exist claims in the patent literature for modifying or preventing hyperopia with, for example, use of filters, dual focus or diffractive lenses, use of TGF-b activation inhibitor, administration of GABA receptor agonists or antagonists, and by limiting the amount of spherical aberration of the eye to less than þ 0.50 D; however, there have been no reports or data from human clinical studies that have considered these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The progressing myopes (defined as 0.25 D progression over the past 2 years) examined in this study exhibited significantly higher amplitude of daily axial length variations and substantially more eye growth over the study period compared to emmetropes, however, it is well known that children exhibit faster rates of eye growth compared to young adults (Zadnik et al, 2003). However, examining the diurnal axial length measurements from ~9 am to ~ 9 pm would not have been logistically possible in a population of young children.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 76%